Review Of Law Enforcement On The Crime Of Murder In Single Organ Night Entertainment - Kesuma, Syukron Ginta; Husin, Budi Rizki; Tamza, Fristia Berdian (Utami Publisher, 2025)
The crime of murder in organ tunggal entertainment is a serious legal violation requiring strict law enforcement. This study examines Decision No. 93/Pid.B/2020/PN Kla, where Defendant I was sentenced to 7 years and 6 months and Defendant II to 2 years and 10 months, as well as Decision No. 353/Pid.B/2023/PN Kla, where Defendant I received 6 years and Defendant II 1 year and 10 months in prison. Both were found guilty under Article 170(2) point 3 of the Indonesian Penal Code. This study analyzes how law enforcement is carried out and what factors hinder the process. A normative and empirical juridical approach was used, with data collected through literature studies and interviews with law enforcement officials, including police investigators, prosecutors, and judges in Lampung Selatan. Data were analyzed qualitatively to provide a comprehensive understanding of the criminal justice system in these cases. The findings show that law enforcement involves police investigations recorded in the Investigation Report (BAP), indictment preparation by prosecutors, and court trials. Hindrances include legal challenges due to complex case conditions, a lack of investigators, limited forensic facilities, public fear of testifying, and cultural preferences for informal conflict resolution. This study recommends improving law enforcement professionalism, establishing forensic laboratories, and increasing public participation in legal processes. Strengthening synergy between law enforcement, adequate facilities, and public awareness is expected to enhance justice and legal effectiveness.